(untitled) (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2011)
Aiming to identify and characterize milk and feeds contamination by mycotoxins it were monitored 96 milk farms in 2009/2010. The study was made in three regions of Paraná state, representatives of dairy production according to report of Ipardes in 2009. Two kinds of data were collected: samples of feedstuff offered to herd, milk, water and in the other hand, production systems data, collected by a guided interview and questionnaire. Toxicology analysis was made according to methodology described by Soares e Rodriguez-Amaya for feedstuff and by ELISA immunoassay kit for aflatoxin M1 – AFM1 in milk. Comparison for regions and seasonal variation of contamination was analyzed by Generalized Linear Models – GLM. Data of milk contamination by mycotoxins and their sources were analyzed under path analysis method. Information collected by questionnaire was related to: storage process, type of feedstuff and supply period of these feeds. Contamination prevalence was 29.2% of all feed samples for mycotoxins. The main contamination by mycotoxins was related to corn and these byproducts (p < 0.05), especially commercial concentrates. On the other hand, aflatoxins were predominant (p < 0.05) over the other mycotoxins metabolites, overall the aflatoxin B1 – AFB1. Milk contamination measured for AFM1 presented seasonal variation (p < 0.05), lower concentrations in rain periods ah higher in dry periods. This can be explained for the increase of concentrates, silage and hay supply in dry period, due to restriction in the forage mass production. There was no effect for regions concerning to AFM1 concentrations, but the range of variation was large, 0.12 to 1.20 μg/L. This shows that the Dairy Production Systems – DPS in farms are widely heterogeneous in terms of practices and this interference in contamination of dairy production by mycotoxins. The main source of milk contamination (AFM1) was the presence of metabolites of aflatoxins in feedstuff, independent of the feed source. Corn and those byproducts have weak direct effect in AFM1 concentrations. This means that the contamination by aflatoxins is generalized among the feed sources and there is no one main source for contamination in analyzed feeds. The major direct effect on AFM1 (0.51) was observed for AFB1, which is reinforced by information available in literature. AFB1 is the major metabolic precursor of AFM1, in mammal’s organisms. We conclude that aflatoxins are the main mycotoxins contaminants in feeds and it is widely spread in all studied regions. There is a seasonal variation in those concentrations in feed, consequently in AFM1 milk levels.